Non-profit organizations in a bureaucratic environment - Paul A. Grout; Wendelin Schnedler (Institute for the Study of Labor (IZA), 2008)
How does the environment of an organization influence whether workers voluntarily provide effort? We study the power relationship between a non-profit unit (e.g. university department, NGO, health trust), where workers care about the result of their work, and a bureaucrat, who supplies some input to the non-profit unit, but has opportunity costs in doing so (e.g. Dean of faculty, corrupt representative, government agency). We find that marginal changes in the balance of power eventually have dramatic effects on donated labor. We also identify when strengthening the non-profit unit decreases and when it increases donated labor.
urn:nbn:de:101:1-2008100833
Keywords: L30; 330; Donated labor; intrinsic motivation; non-profit organizations; power within organizations; Nonprofit-Organisation; Arbeitsangebot; Ehrenamtliche Arbeit; Spende; Soziales Verhalten; Bürokratie; Theorie